Let us converse in arab - Syed Ali; Ali, Syed (UBS Publishers' Distributor New Delhi, 1997)
Let Us Converse in Arabic is a practical guide designed to enhance Arabic language skills through engaging dialogues and cultural insights, fostering effective communication.